2008
DOI: 10.1161/atvbaha.107.158675
|View full text |Cite
|
Sign up to set email alerts
|

CX 3 CR1 Deficiency Impairs Dendritic Cell Accumulation in Arterial Intima and Reduces Atherosclerotic Burden

Abstract: Objective-Dendritic cells (DCs) have recently been found in atherosclerosis-predisposed regions of arteries and have been proposed to be causal in atherosclerosis. The chemokine receptor CX 3 CR1 is associated with arterial injury and atherosclerosis. We sought to determine whether a link exists between arterial DC accumulation, CX 3 CR1, and atherosclerosis. Methods and Results-Mouse aortas were isolated and subjected to en face immunofluorescence analysis. We found that DCs were located predominantly in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 39 publications
(40 reference statements)
4
131
2
1
Order By: Relevance
“…[4][5][6][7] Absence of CX3CR1 (CX3CR1 gfp/gfp , termed CX3CR1 2/2 throughout this manuscript) impeded atherosclerosis development as previously reported. [23][24][25] In addition, it completely prevented an increase of lesion size in renal impairment in all parts of the aortic vessel, namely aortic arch, thoracic, and abdominal aorta ( Figure 1B). Changes in male and female mice were very similar (Supplemental Figure 1, A and B).…”
Section: Absence Of Fractalkine Receptor Cx3cr1 Abrogates Excess Athementioning
confidence: 93%
See 1 more Smart Citation
“…[4][5][6][7] Absence of CX3CR1 (CX3CR1 gfp/gfp , termed CX3CR1 2/2 throughout this manuscript) impeded atherosclerosis development as previously reported. [23][24][25] In addition, it completely prevented an increase of lesion size in renal impairment in all parts of the aortic vessel, namely aortic arch, thoracic, and abdominal aorta ( Figure 1B). Changes in male and female mice were very similar (Supplemental Figure 1, A and B).…”
Section: Absence Of Fractalkine Receptor Cx3cr1 Abrogates Excess Athementioning
confidence: 93%
“…21 CX3CR1 deficiency (CX3CR1 2/2 , mostly studied in CX3CR1 gfp/gfp mice 22 ) decreases the development of atherosclerotic lesions in Apoe 2/2 mice. [23][24][25] This protection is transferred by deficient bone marrow, indicating a major role of myeloid CX3CR1 in lesion development. 26 In Apoe 2/2 and LDLr 2/2 mice, pharmacologic CX3CR1 inhibition moderately decreases aortic root lesion size.…”
mentioning
confidence: 99%
“…20 We are first to show the importance of the CX3CR1 pathway in the generation of heart DC. Unexpectedly, administration of MR1 or CTLA4-Ig did not improve the engraftment of CX3CR1 Ϫ/Ϫ donor hearts.…”
Section: Basic Research Wwwjasnorgmentioning
confidence: 99%
“…For example, it has been demonstrated in several studies that T cells are one of the first cells to invade the arterial intima, later followed by macrophages, DCs, and SMCs in predisposed sites (Xu et al 1990;Kleindienst et al 1993;Millonig et al 2002). However, it has been shown that preexisting vascularassociated dendritic cells (VADCs) are presented in the tertiary lymphoid structures in the aortic adventitia at predisposed sites, even before the invasion of T cells (Bobryshev andLord 1996, 1998;Waltner-Romen et al 1998;Millonig et al 2001a, b;Liu et al 2008;Bobryshev 2010;Cybulsky and JongstraBilen 2010). These DCs can function as antigen-presenting cells (APCs) and thereby capture potentially harmful exogenous or autoantigens and present these to T cells and macrophages.…”
Section: Hsp60 In Human Atherosclerosismentioning
confidence: 99%